SENTENCE PROBLEMS IN THE STUDENTS’ ASSIGNMENT OF DIGITAL STORY TELLING IN WRITING CLASS (Rapunzel and Her Social Media) - Arfiawati, Fristi (Jurnal Sastra - Studi Ilmiah Sastra, 2019)
The Sentence Problems in the Students’ Assignment of Digital Story Telling in Writing Class is the research using a theory proposed by Oshima and Hogue (1981). In addition, this analysis is supported by sintax concept related to the structure of the sentences. This sentence problems comprises of sentence fragments, choppy sentence, run-on sentence and stringy sentence. The method used in this research is the qualitative descriptive analysis. In the analysis, the collected sentences are classified based on its sentence problems, and then analysed based on the constructions and meaning. The results of the analysis show that the sentence problems occured on students’assingment of Digital story telling consist of sentence fragments, choppy sentence, and run-on sentence. There are 4 fragment sentences, 2 choppy sentences and 3 run-together sentences from the data. It shows that the sentence problem mostly occurred on students’ assignments of Digital storytelling is fragment sentence.